Study of serum magnesium levels in type I diabetes mellitus patients: a case control study - Dr. Divya Chaudhary; D., Narayanappa (Pediatric Review: International Journal of Pediatric Research, 2020)
Introduction and background: Magnesium is involved in insulin synthesis. Some studies claim that there is hypomagnesemia in type I diabetes patients and they have implicated its use to increase insulin production, reduce the complications. This study was done to know serum magnesium levels in type I diabetes patients and whether there is any significant correlation between serum magnesium levels and glycemic control. As there are variety of results found in different studies it was important to evaluate serum magnesium levels in type I DM patients and any scope of improvement of insulin levels by its supplementation. Materials and Methods: A case control study was done involving 44 cases, 44 sex and age matched controls. All patients less than 18yrs diagnosed with type I diabetes mellitus were included in study. Serum magnesium levels in cases and controls were compared. Percentage of hypomagnesemia in both groups, correlation between HbA1c levels and serum magnesium levels in cases were calculated. Results: 27.27% of type I DM whereas 11.4% of controls had hypomagnesemia. Mean serum magnesium level in cases and normal controls were 1.83 and 1.88 respectively (p 0.8). Conclusion: Hypomagnesemia in cases was more than double as compared to controls. Although, there was no significant difference between mean serum magnesium levels in cases and controls, no significant correlation between serum magnesium and HbA1C levels was found in cases. Therefore, magnesium supplementation in type I diabetes mellitus for improvement of insulin levels is not recommended.